The Pedagogy of Vulnerability and Marketing Education: Cultivating Self-expansion in a Time of Separation. (April 2023) - Syrdal, Holly A.; Vander Schee, Brian A.; VanMeter, Rebecca A.; Woodroof, Parker J.
Applying the pedagogy of vulnerability and self-expansion theory, the exercise known as the Know Me Activity (KMA) enhances self-expansion by encouraging connections between students and the instructor. The pedagogy of vulnerability is premised on risking self-disclosure as an act of courage. Self-expansion theory is grounded in personal relationships whereby individuals are motivated for personal growth and identify with others to gain access to their resources. In the context of marketing education, self-expansion stems from enhancing student self-awareness for personal growth as well as perceived vulnerability and relatedness of the instructor to encourage access to expertise. The KMA was conducted at three universities and assessed to determine its usefulness as a self-expansion exercise. Survey results indicate that students found the activity contained self-expansion characteristics, and they recommend it for future use. The results of the pretest and posttest analyses also demonstrated an increase in student self-awareness, perceived instructor vulnerability, and perceived instructor relatedness. Self-expansion activities enhance relationships by design and participating in them can lead to increased student effort and persistence. Marketing educators can, therefore, have confidence in utilizing the KMA as a means for mitigating social isolation and encouraging perseverance.